Reversible dementia caused by vitamin B12 deficiency in an older adult - Carrillo Ñañez, Leonidas (2017)
This is the case of an elderly patient with a 40-year history of stomach ulcer, whose relatives perceived behavioral changes for the last two months. Those changes progressively included disorientation, psychomotor agitation, negativism and delirium of persecution, which caused him to be brought to the emergency room. He also showed marked pallor and multiple ecchymosis, due to which he was hospitalized in our service and diagnosed with reversible dementia caused by pernicious anemia. Pancytopenia and neurological changes were also found. The patient responded favorably to the administration of vitamin B12.